Carbapenem vs. Piperacillin-tazobactam for the Treatment of Ceftriaxone-Resistant Gram-Negative Bacteremia: Matched Cohorts by Propensity Score - Rajagopal, Sumanth (Open Forum Infect Dis, 2017)
BACKGROUND: Treatment of bacteremia caused by ESBL producing organisms remains controversial METHODS: Kaiser Permanente Northern California delivers care to 4 million members and is served by a centralized microbiological laboratory and an electronic medical record system. We identified patients hospitalized with a positive blood culture for ceftriaxone-resistant Escherichia coli, Klebsiella species and Proteus mirabilis between January 2008 and December 2015. Patients were grouped as: Piperacillin-tazobactam (PTZ) group: received PTZ (and not carbapenem) OR initial therapy with PTZ followed by a switch to a carbapenem. Carbapenem group: received carbapenem (and not PTZ) OR initial therapy with carbapenem followed by a switch to PTZ. All isolates were ceftriaxone-resistant (surrogate for ESBL production) and susceptible to carbapenems and PTZ by invitro testing. Blood Stream Infection Mortality Risk Score (BSIMRS) was calculated for the 48 hour period of the positive blood culture. Patients in the carbapenem group were matched 1:1 to patients in the PTZ group using a propensity score, which indicated the adjusted probability of being in the carbapenem group. Odds Ratio (OR) was calculated for 14 day mortality. RESULTS: (i) 526 patients identified: 447 E. coli, 40 Klebsiella species, 38 Proteus mirabilis. (ii) Bacteremia source: 375 urinary tract, 82 abdomen, 22 Others (respiratory, wound, skin and soft tissue), line infections, 44 unknown source. Actual Cohort:307 patients in PTZ group, 219 in carbapenem group. Abdominal sources accounted for 63 patients (20.5%) in the PTZ group and 19 (8.7%) in the carbapenem group. Urinary tract accounted for 181 patients (82 %) in the carbapenem group and 194 (63%) in the PTZ group. 110 patients (35.6%) in the PTZ group had a BSIMRS score ≥ 5 compared with 31 (14%) in the carbapenem group. 14 day mortality rate was 41(13%) in the PTZ group; 11 (5%) in the carbapenem group. Matched Cohort: PTZ and Carbapenem treatment groups each had 168 patients and were evenly matched by bacteremia source, BSIMRS score and other covariates. Compared with the carbapenem group, the 14 day mortality rate for the PTZ group had an OR of 1.55 with 95 % CI (0.67, 3.56), p value 0.30. CONCLUSION: 14-day mortality rate was similar between PTZ and Carbapenem groups in matched cohorts developed by propensity score DISCLOSURES: G. T. Ray, Pfizer: Grant Investigator, Research support. Merck: Grant Investigator, Research support.